مراجعةٌ نقديَّةٌ لبعضِ آراءِ الطبري التفسيرية (سورةُ الواقعةِ أنموذجًا): A Critical Review of Al-Tabari’s Interpretive Views: A Case Study of Surat al-Waqi‘ah - AM, Erfandi; Fikri, Mursyid; Husain, Muhammad Zakir (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2025)
This research critically analyzes Imam al-Ṭabarī’s interpretive positions in Jāmiʿ al-Bayān ʿan Taʾwīl Āy al-Qurʾān, particularly where his methodology diverges from conventional Qur’anic exegesis. While renowned for his tradition-based approach (tafsīr bi al-maʾthūr), al-Ṭabarī occasionally questions mutawātir readings or employs figurative interpretations without explicit linguistics or contextual grounds. Employing a descriptive-inductive method, this research examines his views within the frameworks of qirāʾāt, uṣūl al-fiqh, and Arabic linguistics. The findings portray al-Ṭabarī as a balanced scholar who harmonized transmitted knowledge with rational inquiry. His interpretive model exemplifies intellectual moderation and offers a foundation for revitalizing Qur’anic studies through evidence-based engagement that bridges classical heritage with contemporary critical discourse. The research concludes that al-Ṭabarī’s approach embodies intellectual moderation, promoting an evidence-based engagement with classical tafsīr that preserves scholarly heritage while addressing contemporary academic and religious needs. الملخّص تتناول هذه الدراسةُ جملةً من آراء الإمام الطبري التفسيرية في كتابه